Filling model of oil and polar liquid for electrowetting displays based on phase change - Jiang, Hongwei; Qian, Rongzhen; Chen, Wenwen; Zhou, Rui; Zhou, Guofu (Frontiers in Physics, 2022)
Reflective displays have recently attracted more and more attention because of the advantages of low power consumption and eye protection. Among them, electrowetting display (EWD) is the most potential reflective display technology due to its full color and video speed advantages. However, filling models of oil and polar liquids in EWD fabrication were rarely reported. In this paper, a phase change filling model was proposed, and its related equipment was designed and manufactured. The efficiency of phase change filling model has a significant advantage compared to conventional filling models, which can finish the whole process of filling and coupling for 400*500 mm panel within 270 s while the efficiency of other filling models is over 10 min. Since the process of oil filled into the pixels was released into the air environment, the dosing method was significantly enriched, and dosing accuracy was more controllable. The experimental results showed that, a good response time and a high pixel aperture ratio of 31.78 ms and 68.2% can be obtained, respectively.